Optimization of operational control in physical education using digital technologies based on heart rate indicators - Kleymenova M.D. ,; Vitko S.U. ,; Zvyagintsev P.N. ,; Shсherbina A.F. ,; Ivanov V.A. , (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study is to substantiate the capabilities of digital tools in improving the operational control of physical activity during physical education classes. Methods and structure of the study. The study involved girls and boys aged 15-16, who were students of the 10th grade, school GBOU No. 1505 "Preobrazhenskaya". The experiment took place within 5 months within the framework of the Athletics and Skiing blocks. The students were divided into control and experimental groups, in which the contents of the warm-up and the main part of the lesson differed. With the help of a fitness bracelet, the pulse of students was recorded, and using the formulas for the pulse value of exercises, the level of optimal load for each student was calculated. Results and conclusions. The content of the exercises in the experimental group were more optimal and effective than in the control group. Fitness gadgets are an effective tool for teachers to optimize operational control in physical education lessons.